The Psychosufistic Dimensions of Peusijuek: Exploring Spiritual and Psychological Harmony in Acehnese Tradition - Islami, Madinatul; Khodijah, Khodijah; Cecep Soleh Kurniawan (Faculty of Ushuluddin and Philosophy, 2024)
The tradition of peusijuek is a cultural heritage of the Acehnese people that has undergone acculturation with Islamic values. This tradition means asking for coolness, peace, and blessings without contradicting the principles of Sharia law. This study aims to understand the tradition of peusijuek from a psychosufistic perspective, which is an approach that integrates Sufi values and Islamic psychology based on tauhid. The method used is qualitative with a field research approach through participatory and non-participatory observation, interviews, and documentation, which are then analyzed descriptively and analytically. The results of the study indicate that peusijuek not only strengthens the spiritual relationship between humans and God (habl min Allāh) but also reinforces social solidarity (habl min al-nās). This tradition reflects psychosophical values such as gratitude, prayer, mahabbah, khawf, and rajā’, which contribute to the formation of psychological balance and spiritual awareness in society. Thus, peusijuek is not merely a ceremonial ritual but a real representation of relevant psychological and spiritual harmony that needs to be preserved in the face of modern dynamics